Frutas frescas y productos derivados comercializados en el Área Metropolitana de Buenos Aires, Argentina - Puentes, Jeremías Pedro (2020)
This contribution includes the registration of 70 fresh fruit species and their derivative products marketed in the Metropolitan Area of Buenos Aires, Argentina. Data on fruits and derived products were obtained from ethnobotanical fieldwork, where usual qualitative ethnobotanical methodologies were used: participant observation, free listings, open and semi-structured interviews. A bibliographic review was made on the biological activity and effects studied in order to evaluate their correspondence with the assigned local uses. The situation of invisibility/visibility of the treated species was analyzed, according to their circulation in the restricted commercial circuits (Chinese and Bolivian immigrants) and the general commercial circuit. Of the total of 70 recorded species, 62 are visible (89%) and 8 invisible (11%). These last, only found in the Barrio Chino. The registration of marketed fruits, together with their associated knowledge, represents a contribution to the study of local biocultural diversity.